2021
DOI: 10.2147/rmhp.s272234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Coronavirus Disease 2019 Pandemic on an Emergency Department Service: Experience at the Largest Tertiary Center in Taiwan

Abstract: Purpose Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2) is an emerging contagious pathogen that has caused community and nosocomial infections in many countries. This study aimed to evaluate the impact of Coronavirus disease 2019 (COVID-19) on emergency services of the largest medical center in Taiwan by comparing emergency department (ED) usage, turnover, and admission rates before the COVID-19 outbreak with those during the outbreak. Materials and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
1
13
0
2
Order By: Relevance
“…In February 2020, most parameters used to measure the input of patient flow in our ED dropped sharply and reached their lowest point in April. Other tertiary hospitals and the largest healthcare organization in northern Taiwan found that ED visits decreased, similarly, from February to April 2020 [ 29 , 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In February 2020, most parameters used to measure the input of patient flow in our ED dropped sharply and reached their lowest point in April. Other tertiary hospitals and the largest healthcare organization in northern Taiwan found that ED visits decreased, similarly, from February to April 2020 [ 29 , 33 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has posed a dramatic, unexpected, and unprecedented burden on many healthcare systems worldwide. Universally decreased numbers of ED visits by age, disease categories, and the characteristics and case severity of patients have been revealed by anecdotal reports [18][19][20][21][22][23][24][25][26][27][28][29][31][32][33][34][35][36]. Most studies originated from severe pandemic areas that analyzed the change in the early stage (4-8 weeks) of the COVID-19 outbreak and reported a significant decrease, ranging from 31.0 to 63.5%, in ED patient flow compared to a historical control period [18,19,21,23,27,31,34].…”
Section: Impact Of Covid-19 On Ed Attendance In the Initial And Later...mentioning
confidence: 99%
See 1 more Smart Citation
“…This prospective observational study was conducted in the ED of Linkou Chang Gung Memorial Hospital (3406 beds with approximately 15,000 ED visits monthly in 2019), the largest tertiary centre in Taiwan [ 40 , 41 ]. This study was approved by Chang Gung Medical Foundation Institutional Review Board (IRB No.…”
Section: Methodsmentioning
confidence: 99%
“…A new emerging novel virus (SARS-CoV-2) that caused Coronavirus disease 2019 (COVID- 19) was first detected in late 2019, with the possible risk to be transmissible through respiratory droplets and direct contact [1]. In March 2020, the World Health Organization (WHO) declared COVID-19 to be a global pandemic [2].…”
Section: Introductionmentioning
confidence: 99%